A review of neural tube defects at a tertiary neonatal unit in a low-income country with discussion of management challenges in a resource poor setting. (29th September 2015) - Brotherton, H; Jones, U; Pelaez, N; Rodriquez, OR
Abstract : Aims: (1) To describe the demographic and clinical features of neonates with a neural tube defect (NTD) who presented to the tertiary neonatal unit in a low-income country during an eighteen month period. (2) To present the short-term outcomes for these patients following the implementation of surgical management. (3) To discuss the challenges to providing optimal surgical and medical care to this group of patients. (4) To explore preventive strategies for NTDs in the developing world. Methods: A prospective case series of all neonates with a neural tube defect who presented to the only neonatal unit in a low-income country from 1 November 2007 to 30 April 2009. Results: Twenty-two neonates were identified with an age range at presentation of 2 h–10 days. The predominant type of NTD was myelomeningocele (72.7%), 81.3% of which were lumbar-sacral. Eighteen (81.8%) of the NTDs were open and three of these patients had meningitis on admission. 63.6% of neonates had associated hydrocephalus and there was evidence of an underlying genetic syndrome in 22.7%. 72.7% of mothers attended antenatal clinic during the pregnancy but in no cases were folic acid supplements taken before two months gestation. In nearly half of parents there was a history of consanguinity. Corrective surgery was performed on thirteen patients with a postoperative discharge rate of 84.6%. Two patients died post operatively due to sepsis and the mortality for all patients admitted with NTD was 22.7%. Conclusion: Lack of prenatal folic acid and a high rate of consanguinity were the dominant risk factors identified. The majority of cases had open lumbar–sacral myelomeningoceles with associated hydrocephalus. A postoperative mortality of 15.4% is better than reported from other centres in the sub region but hydrocephalus and other neurological complications confer a poor long-term prognosis. Optimal management of neonates with NTD in low income countries is challenging due to a lack of supportive services and qualified personnel. In order to reduce the burden of disease from NTD, preventive strategies such as prophylactic folic acid and maternal education should be encouraged and advocated.